Long-term retention of a divided attention psycho-motor test combining choice reaction test and postural balance test: A preliminary study - Rossi, R.; Pascolo, P.B. (Accident analysis and prevention, 2015)
•We examined unimpaired subjects to study gestures motor retention of a novel psycho-motor test.•Subjects concurrently perform a critical tracking test and a choice reaction test.•We found that only at first exposure three practice trials are needed to learn the test.•Second session of trials shows motor retention but not intersession improvement.•This protocol might be used as a comprehensive impairment test for drivers. Driving in degraded psychophysical conditions, such as under the influence of alcohol or drugs but also in a state of fatigue or drowsiness, is a growing problem. The current roadside tests used for detecting drugs from drivers suffer various limitations, while impairment is subjective and does not necessarily correlate with drug metabolite concentration found in body fluids. This work is a validation step towards the study of feasibility of a novel test conceived to assess psychophysical conditions of individuals performing at-risk activities. Motor gestures, long-term retention and learning phase related to the protocol are analysed in unimpaired subjects. The protocol is a divided attention test, which combines a critical tracking test achieved with postural movements and a visual choice reaction test. Ten healthy subjects participated in a first set of trials and in a second set after about six months. Each session required the carrying out of the test for ten times in order to investigate learning effect and performance over repetitions. In the first set the subjects showed a learning trend up to the third trial, whilst in the second set of trials they showed motor retention. Nevertheless, the overall performance did not significantly improve. Gestures are probably retained due to the type of tasks and the way in which the instructions are conveyed to the subjects. Moreover, motor retention after a short training suggests that the protocol is easy to learn and understand. Implications for roadside test usage and comparison with current tests are also discussed.